Diseño de un plan estratégico, basado en la metodología del balanced scorecard e implementación de un sistema para los principales indicadores del área de ventas de una importadora y distribuidora de calzado de la ciudad de Guayaquil - Benavides Mejía, Candy Melissa (2009)
The thesis that is developed next, was applied in the Importadora y Distribuidora Tello Hnos. dedicated to the commercialization of footwears. The organization adopted the methodology Balanced Scorecard by means of the Strategic Plan,, since they help to translate the strategy in actions whose objective is to convert the vision of short term centered in financial measures in a management based on the long term by means of the use of indicators to address them toward the outlined strategy. They develop six chapters, in which each stage of the Balanced Scorecard is divided, in the chapter I an Introduction of the Balanced Scorecard, in the chapter II the Structure of the Company is described., in the chapters III, IV you begins to apply the methodology Balanced Scorecard when developing the strategic focus in which is carried out an analysis FODA and the identification of the Stakeholders; the transfer of the Balanced Scorecard by means of the determination of the proposal of value, strategic objectives and strategic initiatives. In the chapter V is detailed on the computer system, the dashboard that will be used to complete the strategic objectives. The chapter VI it details the conclusions and recommendations according to the analysis of Importadora y Distribuidora Tello Hnos